2020
DOI: 10.1038/s41598-020-78485-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learned time-signal intensity pattern analysis using an autoencoder captures magnetic resonance perfusion heterogeneity for brain tumor differentiation

Abstract: Current image processing methods for dynamic susceptibility contrast (DSC) magnetic resonance imaging (MRI) do not capture complex dynamic information of time-signal intensity curves. We investigated whether an autoencoder-based pattern analysis of DSC MRI captured representative temporal features that improves tissue characterization and tumor diagnosis in a multicenter setting. The autoencoder was applied to the time-signal intensity curves to obtain representative temporal patterns, which were subsequently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Outside of the framework of TRIPOD, we investigated the reporting on data availability. While six studies [14,32,34,37,38,40] explicitly mentioned data availability upon request, among all twenty-nine examined studies, only Liu et al [39] provided the algorithm code and radiomics data on an open-source platform.…”
Section: Quality Of Reportingmentioning
confidence: 99%
“…Outside of the framework of TRIPOD, we investigated the reporting on data availability. While six studies [14,32,34,37,38,40] explicitly mentioned data availability upon request, among all twenty-nine examined studies, only Liu et al [39] provided the algorithm code and radiomics data on an open-source platform.…”
Section: Quality Of Reportingmentioning
confidence: 99%
“…This edema is additionally suggested to provide local compression of blood flow, further decreasing rCBV when compared with glioblastoma [44,45]. Park et al describe an autoencoder used for DSC that is found to be helpful in differentiating the two diseases by using perfusion patterns [46]. Increased rCBV is additionally suggested to be associated with worse clinical outcomes and shorter overall survivability due to its correlation with aggressive tumor growth in glioblastoma [30,47,48].…”
Section: Dynamic Susceptibility Contrast-enhanced Perfusionmentioning
confidence: 99%
“…The total sample size in the 10 studies was 1311 and the overall accuracy (9 studies), sensitivity, and specificity values of each study was documented. There was no available accuracy value in one of the studies ( 21 ), nor were we able to reverse calculate it with the given information. 5 studies used a 3T MRI scanner, while 3 studies used both 3T and 1.5 T. Two studies ( 22 , 23 ) did not provide details on the scanner used or the scanning protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the authors decided to evaluate only the results of validation/test data set to conduct the statistical analysis in this study. Only one study was externally validated ( 21 ), therefore, all the other included studies were assigned a high risk of bias. As noted previously, future studies of ML should attempt to remove this risk of bias as much as possible, ideally by utilizing a prospective design and external validation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation